Effects of charge double layer and colloidal aggregation on the isotropic-nematic transition of protein fibers in water - Mezzenga, Raffaele (Langmuir : the ACS journal of surfaces and colloids, 2010)
We investigate the effects of variable linear charge density and Debye length on the mesoscopic properties of beta-lactoglobulin fibers in water, by changing the pH and ionic strength, respectively. We determine the isotropic-nematic (I-N) transition by cross-polarized microscopy and quantify by atomic force microscopy the increasing tendency of the fibers to aggregate upon raising ionic strength. We then compare experimental I-N transitions with theoretical expected values based on Onsager theory. Unlike previous reports on lyotropic liquid crystalline behavior of protein fibers, we show that, if double layer effects and aggregation of fibers are correctly included directly in the second virial coefficient and excluded volume, Onsager theory accurately predicts the experimental I-N transition versus pH and ionic strength